Perancangan Sistem Inventaris di Perpustakaan Berbasis Website (Studi Kasus: Perpustakaan SMP Strada Nawar) - Albertus Agung Mahardika; Erick Fernando (KALBISCIENTIA Jurnal Sains dan Teknologi, 2023)
A library is an institution that professionally manages collections of written, printed, and recorded works with a standardized system to meet the users’ needs for education, research, preservation, information and recreation. To manage library collections effectively, a system that can support an inventory of book collections in the library is needed. One of the libraries that requires such a system is the Strada Nawar Middle School Library. By using an inventory system, librarians can record and store related data in the library more easily, such as borrowing data, book collection data, incoming book data, and outgoing book data. This study uses a qualitative method with the system development method using the prototype method and collects data through observation, interviews, documentation and literature review. The results of this study are library inventory applications that are compatible with the existing business processes in the Strada Nawar Middle School Library.